Manajemen Pengembangan Kurikulum Merdeka dalam Meningkatkan Kualitas Hasil Belajar Siswa - Muhammad Pran Yudisti; Dela Darmaleni Zulvi; Isma Yuliza; Ahmad Ridwan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes the management of Merdeka Curriculum development in improving the quality of student learning outcomes through a literature review method. The study examines recent academic sources published between 2023 and 2025 related to curriculum management, Merdeka Curriculum implementation, and student learning outcomes. The findings indicate that the Merdeka Curriculum promotes learning flexibility through differentiated instruction, formative assessment, and the integration of the Pancasila Student Profile Strengthening Project (P5). Effective curriculum management (covering planning, organizing, implementation, and evaluation) plays a crucial role in ensuring successful implementation. Based on the synthesis of previous empirical studies, diverse and flexible learning approaches are reported to enhance student engagement, creativity, and academic achievement, with several studies indicating improvements in learning outcomes ranging from approximately 15–20%. Teachers’ roles as facilitators and designers of contextual learning are identified as key success factors. Overall, effective management of Merdeka Curriculum development contributes to the comprehensive improvement of student learning outcomes.